Respon Komunitas Burung terhadap Beberapa Tipe Habitat pada Ekosistem Artifisial di Wilayah PT. PJB UP Paiton - Kanthi Hardina; Tri Giyat Desantoro; Nuarani Hardikananda; Fajar Alif Sampangestu; Shiela Safitri; Abdul Aziz (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Individual birds that are gathered from several species at one time in a certain room that form a group called the bird community. The composition of vegetation and plant species is a factor that influences the presence of birds in a habitat. The composition of vegetation that occurs due to human intervention forms artificial ecosystems or artificial ecosystems. PT PJB UP Paiton is a national vital object in the form of a power plant area for Java and Bali. The presence of PT PJB UP Paiton formed an artificial ecosystem in the area. The presence of PT PJB UP Paiton formed an artificial ecosystem in the area. Bird community index (BCI) is a technique in determining the quality of an area by using a list of bird species and guilds as indicators. The collection of bird data is carried out by the method of point transects sampling and flora data is carried out by census techniques, namely counting and measuring each individual in each species found in the observation location. Bird species diversity was calculated by Shannon-Wiener diversity index, and evenness index. Plant species diversity is measured by counting the number of species, dominance, diversity index and evenness index of plants while the composition of vegetation is measured by the percentage value of summed dominance ratio (SDR). The results obtained the highest species diversity (H '= 3.05; E = 0.62) at the Housing location and the lowest species diversity (H' = 2.12; E = 0.29) at the Pareho location. M. indica species became the most dominant tree species in housing locations (29.31%) and grocery & dams (42.79%) while office locations were dominated by A. indica trees (26.35%) and pareho by A. saman (26.89%). The results of the analysis of the relationship of vegetation to birds get an r2 value of -0.8 to 0.9 with a significant test value of Pvalue> 0.05. BCI calculation results get the category of low to medium. The highest value (64.4) was obtained at a residential location, and the lowest value (42.8) at an office location.